Moma Titanium Minerals Mine, Mozambique - Mining Technology | Mining News and Views Updated Daily - Mining Technology (Mining-technology, 2021)
Moma, one of the world’s biggest titanium mineral deposits, is located 160km from the city of Nampula in Mozambique, Africa. It is owned and operated by Kenmare Resources. The mine contains the titanium minerals ilmenite, rutile and zircon, which are used as feedstock to produce titanium dioxide pigment. It started production of heavy mineral concentrate (HMC) containing these three minerals in April 2007. It produced 1,201,100t of HMC and shipped approximately 853,100t of finished products in 2020. Kenmare carried out an expansion at the mine ten years ago to fulfil the growing demand for titanium dioxide feedstock in the market. The expansion was aimed to increase the design capacity of the mine by 50% while increasing the mine’s reserve estimate and annual production of HMC. Construction work on the expansion began in December 2010 and the works were completed in December 2013. The expanded mine has a mine life of more than 100 years. The first shipment of concentrated mineral sands was dispatched from Mama in Q2 2019, following the commissioning of the product stream in Q4 2018. The Moma mine had more than 1,420 employees at the end of 2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Extractive Industry Transparency Index 2019-2020 - Mapisse, Inocência; Mate, Rui; Cortez, Edson (Centro de Integridade Pública (CIP) / Public Integrity Centre, 2020)
The extractive industry, particularly the oil and gas sector, has proved promising in the Mozambican economy with potential to contribute to economic growth. It is expected that in the next 3 years the country will show growth in the order of two digits. However, in order to ensure the transmission of growth to economic development based on the exploitation of these resources, there are aspects that should not be ignored such as transparency in governance in the sector. This aspect is also recognized by the government of Mozambique through the Report on Transparency, Governance and Corruption published in July 2019, which emphasizes that the opacity in this sector can give rise to serious conflicts of interest and harm the perception of the population about the real benefits that this industry provides to the country. Although the country is part of the Extractive Industry Transparency Initiative (EITI), whose focus is on the reconciliation of payments made by companies and receipts reported by the Government in the extractive industry sector, there is a gap regarding detailed information on several aspects: tax, social, governmental and other equally relevant and that should be made available on a project-by-project basis.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; transparency / transparência